An approach to identifying novel substrates of bacterial arylamine N-acetyltransferases. - Brooke, E; Davies, S; Mulvaney, A; Pompeo, F; Sim, E; Vickers, R (2003)
Arylamine N-acetyltransferases (NATs) catalyse the acetylation of arylamine, arylhydrazine and arylhydroxylamine substrates by acetyl Coenzyme A. NAT has been discovered in a wide range of eukaryotic and prokaryotic species. Although prokaryotic NATs have been implicated in xenobiotic metabolism, to date no endogenous role has been identified for the arylamine N-acetyl transfer reaction in prokaryotes. Investigating the substrate specificity of these enzymes is one approach to determining a possible endogenous role for prokaryotic NATs. We describe an accurate and efficient assay for NAT activity that is suitable for high-throughput screening of potential NAT ligands. This assay has been utilised to identify novel substrates for pure NAT from Salmonella typhimurium and Mycobacterium smegmatis which show a relationship between the lipophilicity of the arylamine and its activity as a substrate. The lipophilic structure/activity relationship observed is proposed to depend on the topology of the active site using docking studies of the crystal structures of these NAT isoenzymes. The evidence suggests an endogenous role of NAT in the protection of bacteria from aromatic and lipophilic toxins.